INDEKS ATEROGENIK PLASMA DI INFARK MIOKARD AKUT DAN PENYAKIT DIABETES MELITUS (Atherogenic Index of Plasma in Acute Myocardial Infarction and Diabetes Mellitus) - Zulfikar Indra; Suci Aprianti; Darmawaty E.R. (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Diabetes Mellitus (DM) is associated with an increased cardiovascular risk. Atherogenic Index of Plasma (AIP) is a strong predictorof myocardial infarction. The aim of this study was to know the difference of AIP in acute myocardial infarction (AMI) with and withoutDM. This study was conducted by cross sectional method using data from the medical records of AMI patients at the Dr. WahidinSudirohusodo Hospital, Makassar during January 2010 up to May 2013. The AIP values were calculated by the [log (TG: HDL-C)]formula. All data were classified into two groups. The data were then analyzed by unpaired T test. In this study, AMI was mostly foundin the 50–59 years group, 33.63%. The AIP in AMI with DM was higher than without DM (0.69±0.26 vs 0.57±0.26, p=0.001). TheAIP in AMI with and without DM was higher in the female than the male group (0.63±0.24 vs 0.62±0.28. P=0.58). The AtherogenicIndex of Plasma in AMI with DM was higher than without DM. Based on this study, it can be concluded, that AIP can be used as thepredictor of cardiovascular risk in diabetes patients.